Globalisation and enlargement of the European union : Austrian and Swedish social forces in the struggle over membership - Bieler, Andreas, 1967- (Routledge/Warwick studies in globalisation, 2000)
On January 1 1995, Austria and Sweden joined the European Union (EU). This book examines why these two countries joined at such a moment and studies their accession against the structural background of globalization. In this cutting-edge analysis, Andreas Bieler argues that conventional neo-functionalist and intergovernmentalist theories fail to explain such structural change as they take existing power structures as given. Therefore, he develops a neo-Gramscian perspective as an alternative approach to European integration.